Plasmacytoid myoepithelioma arising in hard palate – A rare case report - Trupti V Gaikwad; Mahesh S Chavan; Vikram V Khare; Charusheela R Gore (Journal of Indian Academy of Oral Medicine and Radiology, 2022)
Myoepithelioma, which is benign, is a salivary gland neoplasm representing 1.5% of all the neoplasms of salivary glands. The commonest location of its occurrence is parotid gland. In this condition, there is proliferation of myoepithelial cells arranged in cords, mantles, or nests. A 20-year-old woman presented with a well-circumscribed, asymptomatic swelling on the left half of the hard palate, which was gradually increasing in size for 10 years. A provisional diagnosis of pleomorphic adenoma was made. Computed tomography scan showed a well-defined soft tissue density lesion, which on histopathologic examination revealed a well-circumscribed, partially encapsulated neoplasm comprising monomorphic tumor cells in clusters and lobules with plasmacytoid characteristics. Therefore, it is necessary to consider myoepitheliomas also as one of the differential diagnoses while dealing with palatal swellings.